Development of reinforced thermoplastic elastomer with kenaf bast fibre for automotive component - Anuar, Hazleen; A., Adilah; S.N., Surip (2010)
This paper compared mechanical properties of kenaf fibre (KF) composites in different matrix systems namely; thermoplastic natural rubber (TPNR) and polypropylene/ethylene-propylene-diene-monomer (PP/EPDM). Both composites were produced via melt blending method using Haake internal mixer, and then compression moulded. The ratio of thermoplastic:elastomer was 70:30 for both polymer blends. The composites were reinforced with 20% kenaf fibre by volume. In addition, maleic anhydride polypropylene (MAPP) was also added as a compatibilizer in the case of treated composite. From the tensile tests, it was found that the tensile strength for TPNR is about 12% higher than the PP/PPDM matrix system. However the present of KF and MAPP has significantly increased the tensile strength of the PP/EPDM composite by approximately 81% while only 55% increment attained in TPNR-KF-MAPP as compared to unreinforced TPNR. This shows that KF has imparted its strength to the PP/EPDM system with good interaction provided by the compatibilizer agent. From the scanning electron micrographs (SEM), it has revealed that the improvement achieved in mechanical properties was due to the interaction between both matrix systems and kenaf fibre. As a conclusion, development of reinforced PP/EPDM with kenaf fibre has a potential to be applied as automotive component.